Comparative Analysis of Laparoscopic Inguinal Hernia Repair in Neonates and Infants. Issue 5 (October 2020) - Walsh, Caoimhe M.; Ng, Jessica; Saxena, Amulya K.
Abstract : Background: This study analyzed our cohort of infants (age below 12 mo) who underwent laparoscopic inguinal hernia repair (LIHR), comparing those 3 months and below (corrected premature) to above 3 months (term infants) corrected age at the time of surgery. Materials and Methods: Retrospective analysis of a single surgeon and associated trainees' experience of LIHR in infants below 12 months over a 5-year period (2013-2018) was performed. The operative technique involved a 5-mm scope and 3-mm instruments for herniorrhaphy with 4/0 Prolene purse-string suture. Data collected included patient demographics, prematurity (<37 wk), corrected age and weight at surgery, preoperative hemoglobin level, comorbidities, anesthetic time, major perioperative complications, and inguinal hernia recurrence. A comparison was made between those operated at 3 months and below and above 3 months corrected age. Perioperative issues affecting infants 3 months and below were identified and analyzed. Statistical analysis includes T test and Fisher exact test ( P <0.05 significance). Results: Eighty infants underwent LIHR (age below 12 mo), of which 67 (84%) were male with a median corrected age of 10.5 (range 2.5 to 44) weeks, the median weight of 5.5 kg (range 2.1 to 10.8). A total of 47 (59%) infants had a unilateral inguinal hernia repair and 33 (41%) had a bilateral repair. The median anesthetic time was significantly greater for infants 3 months and below at 93 (range 61 to 125) minutes, compared with 83 (range 47 to 146) minutes for the above 3 months age group ( P =0.001) There were no perioperative complications or mortality. One patient had a recurrence of an inguinal hernia. Low hemoglobin levels, comorbidities, and extreme prematurity required more attention during preoperative assessment and postoperative management. Conclusions: Comparable cohorts demonstrated no significant difference in recurrences despite significant differences in weight and median anesthetic time. Preoperative hemoglobin is an important factor that needs to be addressed in infants 3 months and below for scheduling the procedure date (transfusion vs. iron supplementation).